A study to assess the health care utilization and the activities of the daily living status amongst the geriatric population residing in urban and rural field practice areas of a medical college in Tamil Nadu - Karthikeyan, S.; Rajan, T. Palanivel; Raghuram, V.; Pandi, S. (International Journal Of Community Medicine And Public Health, 2024)
Background: The prevalence of disability in the activities of daily living (ADL), could probably have a significant impact on the healthcare utilization amongst the geriatric population with disability. Methods: A cross-sectional study in the urban and rural field practice areas of a medical college in Tamil Nadu, using a sample size of 402 elderly individuals. Using the pre-tested, semi-structured questionnaire; the socio-demographic variables, healthcare utilization variables and a comprehensive Katz ADL assessment were used. Results: The overall prevalence of ADL limitation amongst the elderly was seen in 49 (12.2%) elderly individuals mostly with a score of 5 (mildest form) was found in 36 (74%) of the elderly. There was an association found between the follow-up care at health centres, frequency of visits, distance from home to health centres and the ADL limitation with a P- value less than 0.05 (C.I.-95%) using the Pearson chi-square test using SPSS v.26.0. Conclusions: The association between ADL limitation and healthcare utilization calls for initiatives at the family and community level.